Towards the investigation of ternary compound in the Ti-Al-Zr-O system: Effect of oxygen fugacity on phase formation. Issue 10 (August 2020) - Bekker, T.B.; Litasov, K.D.; Shatskiy, A.F.; Sagatov, N.E.; Krinitsin, P.G.; Krasheninnikov, S.P.; Podborodnikov, I.V.; Rashchenko, S.V.; Davydov, A.V.; Ohfuji, H.
Abstract: The Ti-Al-Zr-O system has received significant attention as it hosts a variety of phases of industrial interest. In this paper, new experiments on the Ti-Al-Zr-O system aimed at clarifying phase formation depending on the redox conditions with special attention to the formation of ternary compounds and their results have been reported. For the first time a monophase AlTi2 O5 sample with a ratio of titanium oxides TiO2 :Ti2 O3  = 2:1 was obtained and characterized. Single-crystal X-ray diffraction analysis of β-(Zrx Ti1-x )2 O4 crystals was carried out. The synthesis of the ternary Ti-Al-Zr compound was performed in an evacuated quartz ampoule and accompanied by the extraction of silicon from the ampoule. The compound has pyrochlore-type cubic structure A2 4+ B2 3+ O7 ( Fd- 3 m ) and the composition close to (Ti 4+ 1, 47(2) Zr0.41(2) Si0.12(1) )2 (Al1.15(4) Ti 3+ 0.85(4) )2 O7 . We believe that our study is a starting point for future research as it provides first experimental data on the ternary compound in the Ti-Al-Zr-O system.